2013
DOI: 10.1007/s11999-012-2608-9
|View full text |Cite
|
Sign up to set email alerts
|

Have Bilateral Total Knee Arthroplasties Become Safer?: A Population-Based Trend Analysis

Abstract: Background Studies suggest a trend in the selection of younger and healthier individuals to undergo bilateral TKAs in an attempt to diminish the incidence of complications. It remains unclear whether this development has reduced overall perioperative morbidity and mortality.Questions/purposes We investigated whether changes in demographics and comorbidity patterns of patients undergoing bilateral TKAs are detectable and coincide with changes in length and cost of hospitalization, incidence of perioperative com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 18 publications
3
19
0
Order By: Relevance
“…However, the type of TKA, such as SD BTKA or St BTKA, was not identified as a risk factor in this study cohort of patients for whom the type of TKA was chosen based on age and ASA classification. Our findings agree with those of several previous studies reporting that an increased risk for postoperative complications was associated with ASA score of 3 or 4, preoperative cardiovascular disease, and older age [8,15,18,24,[29][30][31][32][33][34][35][36][37]. Our data, together with the data of these previous studies, suggest that if patients are properly selected, the type of BTKA procedure, such as SD BTKA and St BTKA, may not increase the risk of postoperative complications and has a risk comparable to the risk of UTKA.…”
Section: Discussionsupporting
confidence: 91%
“…However, the type of TKA, such as SD BTKA or St BTKA, was not identified as a risk factor in this study cohort of patients for whom the type of TKA was chosen based on age and ASA classification. Our findings agree with those of several previous studies reporting that an increased risk for postoperative complications was associated with ASA score of 3 or 4, preoperative cardiovascular disease, and older age [8,15,18,24,[29][30][31][32][33][34][35][36][37]. Our data, together with the data of these previous studies, suggest that if patients are properly selected, the type of BTKA procedure, such as SD BTKA and St BTKA, may not increase the risk of postoperative complications and has a risk comparable to the risk of UTKA.…”
Section: Discussionsupporting
confidence: 91%
“…Risk factors for poor inhospital outcomes included older age and comorbidities such as congestive heart failure, pulmonary hypertension, renal failure, cardiac valve disease, and coagulopathies. In a separate report involving the Nationwide Inpatient Sample database, Memtsoudis et al specifically examined the yearly incidence of in-hospital mortality and morbidity among patients who underwent simultaneous bilateral total knee arthroplasty between 1999 and 2008 27 20.011]). They concluded that the significant decrease in in-hospital mortality may have been related to improvements in perioperative care, such as an expanded role for telemetry.…”
Section: Administrative Datamentioning
confidence: 99%
“…The number of TKAs performed in the United States has been steadily increasing. Most recently, approximately 6% of all TKAs performed were bilateral TKAs (BTKAs) [32]. Considerable controversy exists surrounding various aspects of the practice of same-day BTKAs [28,39].…”
Section: Introductionmentioning
confidence: 99%